Optimal valuation framework for M&A decision -a case study - LU, JIA YUN (2009)
As the trend of merger and acquisition has gradually emerged in Asia and the world during the 20th century, the study is motivated to analyze the valuation framework behind each merger and acquisition activity (M&A). Since a cross-border merger and acquisition is suggested to facilitate firms to adjust environmental transformation easily with the aid of international expertise, it is generally believed that firms can also obtain certain competitive advantages through the transaction. In particular, firms in highly competitive environment may continuously adopt takeover strategies in order to early entry the target markets.